Socio-Economic Empowerment of Women - Sharma, Neha (Journal of Commerce and Trade, 2009)
Women’s empowerment in India is challenging task as we need to acknowledge the fact that the gender based discrimination is a deep rooted social malice practiced in India in many forms since thousands of year. Women’s education in India plays a very important role in the overall development of half of the human resources but improving the quality of life at home & outside. Although most women in India work & contribute to the economy in one form or other much of their work is not documented or accounted for in official statistics. We can say that women are equally competitive to men & even surpassing the men. There is no field today where is not approaching. Women have posed a threat to the success of the men. When we talk about women empowerment in India the most important aspect that comes into the mind is attitude of the society towards women. Women are still considered as burden & liabilities. Violence against women is not a myth but a reality. It is a global phenomenon. The development of the country is not possible if women, comprising half of the human resources as labour force & citizens stay away from the national development process.